Sirisuk Smart Market: livelihood on the new normal in sustainable development goal of Surat Thani Municipality, Surat Thani Province, Thailand - Muhamad, Chettha; Jaihawweerapong, Damrongpan; Khaenamkhaew, Daycho; Patoom, Boonying; Jeawkok, Jirachaya; Tudkuea, Tanyakorn; Sriphong, Chompunuch (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The purpose of this article was to study the performance of Sirisuk Smart Market: livelihood on the new normal in the sustainable development goal of Surat Thani Municipality, Surat Thani Province, Thailand. According to the conceptual framework related to sustainable development, from the study of the theory, a literature review, and interviews with 29 representatives of various groups involved in the operation of Smart Market, which were used to analyze the content and write a descriptive description. The results of the study found that Surat Thani Municipality is a large local government organization with high performance with a population of more than 130,000 representatives, and Smart Market is a project that the people of the Sirisuk community have participated in together according to the principle of participation and receive benefits. In addition, good governance principles are applied in operations. By focusing on working with “law, morality, transparency, participation, sense of responsibility, and worthiness.”